Perbandingan Efektifitas Rapid Diagnostic Test (Rdt) Dengan Pemeriksaan Mikroskop Pada Penderita Malaria Klinis : Di Kecamatan Jaro - Rakhman, M. Aulia; Istiana, Istiana; Al Audhah, Nelly (Pendidikan Dokter Universitas Lambung Mangkurat, 2013)
ABSTRACT: Malaria is a disease caused by genus Plasmodium. Enforcement of the diagnosis malaria is microscopic examination of thick blood droplets and thin blood droplets and examination of Rapid Diagnostic Test (RDT). Gold standard for the diagnosis of malaria is microscopic examination. Rapid Diagnosis Test (RDT) is one alternative diagnostic tool in detecting Plasmodium quickly and doesnât require special skill. The purpose of this study was to discover the effectiveness of Rapid Diagnostic Test (RDT) compared with microscopic examination in patient with clinical malaria in Jaro Sub-district. This study was a descriptive analytic study using the data of the result of malaria examination means of microscope examination and RDT on January â June 2012, with cross sectional approach. RDT examination result showed 98% sensitivity value, 100% specificity value, 100% positive predictive value and 98% negative predictive value compared with microscopic examination. Statistical test using Mc.Nemar test with 95% level of confidence interval p=0,125 (p>0,05). This show was no difference in the effectiveness of RDT examination and microscopic examination of patients with clinical malaria in Jaro Sub-district.Keywords: effectiveness, Rapid Diagnostic Test (RDT), microscopic examinationABSTRAK: Malaria adalah penyakit yang disebabkan oleh genus Plasmodium. Penegakkan diagnosis malaria adalah dengan pemeriksaan mikroskopis berupa tetesan darah tebal dan tetesan darah tipis serta pemeriksaan Rapid Diagnostik Test (RDT).Â Gold standard untuk diagnosis malaria adalah dengan pemeriksaan mikroskopis. Rapid Diagnosis Test (RDT) merupakan salah satu alat diagnostik alternatif dalam mendeteksi Plasmodium secara cepat dan tidak memerlukan keterampilan khusus. Tujuan penelitian ini untuk mengetahui efektifitas Rapid Diagnostic Test (RDT) dibandingkan dengan pemeriksaan mikroskop pada penderita malaria klinis di Kecamatan Jaro. Penelitian ini merupakan penelitian deskriptif analitik menggunakan data hasil pemeriksaan malaria melalui pemeriksaan mikroskop dan RDT selama bulan Januari â Juni 2012 dengan pendekatan cross sectional. Hasil penelitian menunjukkan pemeriksaan RDT memiliki nilai sensitivitas 98%, spesifisitas 100%, nilai duga positif 100% dan nilai duga negatif 98% dibandingkan dengan pemeriksaan mikroskopis. Analisis uji statistik menggunakan uji Mc.Nemar dengan tingkat kepercayaan 95% didapatkan nilai p=0,125 (p>0,05)S. Hal ini menunjukkan tidak terdapat perbedaan efektifitasÂ pemeriksaan RDT dan mikroskopik pada penderita malaria klinis di Kecamatan Jaro..Â Kata-kata kunci: efektifitas, Rapid Diagnostic Test (RDT), pemeriksaanÂ mikoskopisABSTRACT: Malaria is a disease caused by genus Plasmodium. Enforcement of the diagnosis malaria is microscopic examination of thick blood droplets and thin blood droplets and examination of Rapid Diagnostic Test (RDT). Gold standard for the diagnosis of malaria is microscopic examination. Rapid Diagnosis Test (RDT) is one alternative diagnostic tool in detecting Plasmodium quickly and doesnât require special skill. The purpose of this study was to discover the effectiveness of Rapid Diagnostic Test (RDT) compared with microscopic examination in patient with clinical malaria in Jaro Sub-district. This study was a descriptive analytic stud